Reconsidering Authenticity in Religious Revival and Renewal in Japan: Theoretical Considerations - Law, Jane Marie (Acta Orientalia Vilnensia, 2003)
This article is a discussion of the current dominant theoretical paradigms being used by scholars to delineate the processes of revival in Japanese “folk performing arts”. Law identifies a theoretical debate, often cast as an either/or proposition, between a critical assessment of the nativist claims being made by scholars in the folklore movement in Japan, and the naive historicism of the folklorists, who have, nevertheless, accurately identified the fragile nature of many of Japan’s performing arts traditions. Law argues that people involved in “reclaiming” performing arts traditions are far from the mindlessly loyal national patriots of a larger nativist discourse we read about in the minzokugaku (folklore) scholars. Nor are they the nostalgic subject, finding their sense of identity through a desperate appeal to a vanished, fragmented past remembered through a tumultuous and shifting present, suggested by the critical theorists. They have a considerably greater degree of agency than current available theoretical paradigms give them credit for. There is a ludic quality to their performing the past in the present, crafting what is meaningful, and what is now local. It is attention to this quality of agency in how people understand dislocations of the local, its reconstitution in their new communities, and the inclusion of reflections on the past and the meaning of their lives in the continuum of time - beyond our own significations of these processes as folklorists (popular religion scholars) or Critical scholars of religion - that informs this article. The article presents the assumptions of each of these basic paradigms, and then moves to a discussion of four interlocking themes upon which each of these paradigms is dependent: 1) the idea of the local; 2) the category of the authentic; 3) nationalism and 4) nostalgia. Law suggests that while both theoretical tendencies, the critical and the historicist/preservationist are out of touch with what is happening in communities in Japan where “local” performing arts are being revived and reenacted. The article suggests that we need to shift our theoretical attentions from discussions of authenticity, nostalgia, localism and nationalism and begin to explore how people are actively adapting to a more global reality in rural Japan.